Genotype Analysis of ABCC1, NCF4 and CBR3 Polymorphism and the Association With Childhood Acute Lymphoblastic Leukemia in Mexican Childhood Population - Gándara-Mireles, Jesús Alonso; Lares-Asseff, Ismael; Reyes Espinoza, Elio Aarón; Blanco, Javier G.; Chairez Hernández, Isaias; Córdova Hurtado, Lourdes Patricia; Loera Castañeda, Verónica; Patrón Romero, Leslie; Venzor Sánchez, Cristina; Payan Gándara, Hugo; Arechiga Gurrola, Dinora; Almanza Reyes, Horacio (Frontiers in Pharmacology, 2021)
BACKGROUND:The identification of genetic risk factors for Acute Lymphoblastic Leukemia (ALL), are increasingly urgent and necessary. OBJECTIVE: Determine the association of the genetic polymorphisms ABCC1 rs3743527, NCF4 rs1883112 and CBR3 rs1056892 with ALL. METHODS: DNA samples were obtained in 71 children with ALL (from 2 to 18 years) and in 71 controls without ALL, to determine the polymorphisms by real-time polymerase chain reaction (qPCR), using specific TaqMan probes in a StepOne® thermal cycler (Applied Biosystems, USA). RESULTS: The results of the Odds Ratio analysis show that in the rs1883112 polymorphism of the NCF4 gene, the heterozygous allele has a risk effect for ALL (OR = 3.1870, CI = 1.8880 to 7.9383 and p = 0.0002), in turn the mutated genotype (AA) is associated with a protective effect (OR = 0.26, 0.1248 to 0.5434 and p = 0.0003). On the other hand, the CBR3 rs1056892 polymorphism shows a significant association of risk to ALL, in the presence of the HT genotype (OR = 2.77, IC = 1.3837 to 5.5651 and p = 0.004) and the mutated genotype of this polymorphism has a significant association with protection to ALL in the HM genotype (OR = 0.52, IC = 0.2639 to 1.0304 and p = 0.05). While the inheritance models of the polymorphisms let us see that of the rs1883112 polymorphism of the NCF4 polymorphism; the HT genotype of the codominant model shows a protective effect against ALL (OR = 0.4117, IC = 0.1718 to 0.9866 and p= 0.04), the recessive model shows us and confirms what we already saw in table number 3, since there is an association with protective effect in the HM genotype (OR = 0.2604, IC = 0.1248 to 0.5434 and p = 0.0003). In the polymorphism rs1056892 of the CBR3 gene, a protection association was found in the heterozygous allele of the codominant model (OR = 0.3448, IC = 0.1375 to 0.8896 and p = 0.0274) .In addition, the recessive inheritance model for the HM genotype shows a protective effect to ALL, (OR = 0.52, CI = 0.9919 to 3.8638 and p = 0.05).